Effect of intramuscular treatment with different iron dextran dosages and non-inferiority study to gleptoferron - Isabel Hennig-Pauka; Martin Ganter; Dirk Bornhorn; Wesley Lyons; Enric Marco; Glen Almond; Bettina Schneider; Lothar Kreienbrock; Ken Steen Pedersen (Acta Veterinaria Scandinavica)
Abstract Background Prevention of iron deficiency in suckling piglets by intramuscular injection of a standardized amount of iron dextran or gleptoferron in the first days of life can lead to over- or underdosage with respective health risks. Currently, combined iron products containing an active substance against coccidia are also used on farms. When using a combination product targeting two diseases, an adjustment of the necessary amount of iron to prevent anaemia in the frame of a farm-specific treatment protocol is not possible. The aim of this study was to test if iron dextran, which can be used in flexible volumes, is statistically non-inferior to a combinatory product, containing gleptoferron and toltrazuril. In addition, different administration schemes for iron dextran with respect to time point and dosage were compared on a conventional farm. Within each out of 17 litters eight healthy piglets were allocated to one of the four treatment groups on the second day of life: (1) 200 mg iron dextran, (2) 200 mg gleptoferron and 45 mg toltrazuril in combination, (3) 300 mg iron dextran, (4) 200 mg iron dextran and additional intramuscular administration of 200 mg iron dextran on day 11 of life. Pigs of groups 1, 3 and 4 received toltrazuril orally. Red blood cell measures were determined prior to treatment on day 2 of life and at weaning. Body weights were measured on day 2, 24, 74 and 160 of life. Results Iron dextran was non-inferior compared to gleptoferron within a tolerance range of ± 5 g haemoglobin/L. In total, treatment groups did not differ with respect to red blood cell parameters and average daily weight gain. The 50% pigs with intermediate birth weights profited from an additional iron dextran administration with respect to higher haemoglobin concentrations at weaning. Conclusions In this investigation gleptoferron and iron dextran appear equally appropriate for prevention of iron deficiency anaemia. Piglets of different birth weights might profit differently from an additional iron administration, so that usage of a product containing iron as a single substance is of advantage to allow a flexible adjustment of dosage during the suckling period.